Study of the chromite mineralization associated to ophiolites from Tinos Island, Attico-Cycladic Massif - Kokkaliari, Maria; Seymour, Karen St.; Tombros, Stylianos F.; Koutsopoulou, Eleni (Bulletin of the Geological Society of Greece, 2019)
This paper aims to study the chromitites, as well as their host rocks (meta-peridotites, meta-dunites and serpentinites) of the ophiolite complex of Mount Tsiknias, in Tinos Island. Recognition of their mineralogy and their textural features was carried out through detailed petrographic study. The mineral chemistry analysis contributed to the evaluation of the analyzed chromites, the chemical composition of which provides important information about the petrogenetic evolution of the chromitite ores. The chromites were in equilibrium with boninite melts derived from Supra-Subduction Zone, e.g., a depleted mantle wedge. In the binary classification diagram for spinels, the Tinos samples extend in the fields of Mg-chromite and chromite sensu strictu. In the TiO2 vs Al2O3 diagram, the chromites plot in the field of Supra-Subduction Zone (SSZ) peridotites and partly overlap the field of chromites in Back-Arc Basalts (BABB), however the same samples plot in the field of chromite of boninites. In the Al2O3 vs Cr2O3 diagram both groups of Tinos chromites plot in the field/extremity of “mantle chromites”.